1993
DOI: 10.1002/ijc.2910530114
|View full text |Cite
|
Sign up to set email alerts
|

Fundal atrophic gastritis as a risk factor for gastric cancer

Abstract: The role of atrophic gastritis of the gastric corpus (fundal atrophic gastritis) as a high-risk factor was investigated by studying operative findings and follow-up data on 690 patients with benign gastric diseases recorded at the Osaka Cancer Registry. The extent of fundal atrophic gastritis was determined by the endoscopic Congo red test. The patients were followed-up from the time of endoscopic examination (1968 to 1976) to December 31, 1987. The vital status of 654 patients (94.8%) at the end of the observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
3
6

Year Published

1993
1993
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 17 publications
3
77
3
6
Order By: Relevance
“…Several previous studies have demonstrated that the more advanced the stage of H. pylori-related CAG, the greater the cancer risk. 31,32,[40][41][42][43][44] Subjects with metaplastic gastritis, an end result of long-lasting H. pylori infection, are thus considered to be at particularly high risk of gastric cancer. Indeed, our previous longitudinal cohort study found that a group of middle-aged male subjects with metaplastic gastritis based on 2 serum tests-negative results for H. pylori antibody and positive results on the PG test-displayed an annual cancer incidence rate of about 0.87%, meaning that 1 cancer developed in 11.5 subjects during every 10-year period.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have demonstrated that the more advanced the stage of H. pylori-related CAG, the greater the cancer risk. 31,32,[40][41][42][43][44] Subjects with metaplastic gastritis, an end result of long-lasting H. pylori infection, are thus considered to be at particularly high risk of gastric cancer. Indeed, our previous longitudinal cohort study found that a group of middle-aged male subjects with metaplastic gastritis based on 2 serum tests-negative results for H. pylori antibody and positive results on the PG test-displayed an annual cancer incidence rate of about 0.87%, meaning that 1 cancer developed in 11.5 subjects during every 10-year period.…”
Section: Discussionmentioning
confidence: 99%
“…As several studies dealing with endoscopic biopsies or chromoendoscopic testing have found that progression of chronic atrophic gastritis (CAG) increases the risk of cancer (Meister et al, 1979;Sipponen et al, 1985;Siurala et al, 1966;Tatsuta et al, 1993;Testoni et al, 1987), accurate and reliable evaluation of the extent of CAG is considered important for identifying individuals at high risk of cancer. However, accurately diagnosing the extent of CAG based on a few biopsy samples is difficult, because CAG together with intestinal metaplasia is a multifocal process.…”
Section: Serum Pg Testmentioning
confidence: 99%
“…CAG of the antrum and corpus are independent risk factors for gastric cancer, and the risk increases exponentially with the increase in grade and severity of atrophy (6,7). The progression of severe fundal atrophic gastritis to gastric cancer was documented to be ~3% from a total of 654 patients in the Japan (8). Annual surveillance of patients with IM or atrophic gastritis detected a higher percentage of gastric cancer, at 11% (9).…”
Section: Introductionmentioning
confidence: 99%